Endowing improved osteogenic activities with collagen membrane by incorporating biocompatible iron oxide nanoparticles - Li, Zheng; Zhang, Yunyang; Ye, Qing; Wang, Lei; Chen, Hui; Xu, Chenhui; Wang, Peng; Sun, Jianfei (Frontiers in Bioengineering and Biotechnology, 2023)
Collagen-based scaffolds, renowned for their exceptional biocompatibility, have garnered attention as promising scaffolds for advancing bone tissue regeneration. Nevertheless, these scaffolds possess inherent limitations, such as notably compromised osteo-conductivity and osteo-inductivity.To address this matter, our study focused on enhancing the mechanical properties and osteogenic bioactivities of bovine-derived collagen membranes (CMs) from Achilles tendon by incorporating FDA-approved iron oxide nanoparticles (IONPs), termed as IONPs-CM. Three types of IONPs-CM (IONPs-CM-0.5, IONPs-CM-1, and IONPs-CM-1.5) were constructed by altering the amounts of feeding IONPs. Surface topography analysis demonstrated comparable characteristics between IONPs-CM and neat CM, with the former exhibiting augmented mechanical properties. In vitro evaluations revealed the remarkable biocompatibility of IONPs-CM towards mouse calvarial pre-osteoblast